Single-Stage Surgery Using Calcium Sulfate Pellets in Association with Tumor Resection as Treatment for Intraosseous Hemangioma of the Radius Shaft in a 2-Year-Old Boy - Andreacchio, Antonio; Alberghina, Flavia; Giacometti, Vanessa; Marengo, Lorenza; Canavese, Federico (Journal of Hand and Microsurgery, 2017)
Intraosseous hemangiomas are uncommon benign vascular tumors. Here the authors report a case of intraosseous hemangioma of the radial shaft in a 2-year-old boy, surgically treated by tumor mass resection and application of calcium sulfate pellets with no signs of relapse over a 2-year follow-up. Moreover, the lesion healed with new bone formation, and the last plain radiographs suggested homogenous normal trabecular bone density. The radius grew in length and remodeled to an almost normal shape. Clinically, elbow flexion-extension and forearm pronation and supination were within normal limits at the last follow-up visit.This report points to calcium sulfate pellets as a valid alternative to autologous bone grafting as void filler in large bone defects. Calcium sulfate pellets enable fast osteoinduction without interfering in follow-up imaging.
Keywords: intraosseous hemangioma; pathologic fracture; calcium sulfate pellets; bone substitute